Clinical profile of COVID-19 patients admitted in a tertiary care hospital of Nepal: A descriptive cross-sectional study - Poudel, Sujan Chandra; Poudel, Shekhar; Shrestha, Prinsa; Bhattarai, Tulsi Ram; Mishra, Aakash (Journal of Kathmandu Medical College, 2022)
Background: Coronavirus disease 2019 (COVID-19) causes mild to severe respiratory illness and is associated with ICU admission and mortality. Since data regarding clinical profile of COVID-19 patients in Nepal is still lacking, it is important to study clinical behaviour of COVID-19 in Nepal. In this study the demographic profile, clinical features, lab parameters, and outcomes in hospitalised COVID-19 patients in a tertiary care hospital are reported. Objective: To assess the clinical profile in terms of clinical symptoms, laboratory parameters, and outcome of COVID-19 admitted patients in a tertiary care hospital. Methods: This is a descriptive cross-sectional study conducted at KMCTH, from June 1, 2021 to July 31, 2021 after taking ethical clearance from institutional review committee. All patients infected with COVID-19 admitted in this hospital, from June 1, 2021 to July 31, 2021 were included by convenience sampling. Data were collected, and entry and analysis were done in Microsoft Excel Sheet 2007. Results: During the study period, 245 COVID-19 patients were admitted and were included in the study. The median age of the patients was 55 years, the mean age was 55 ± 17 years, and 139 (56.74%) were male. The common presenting complaints were cough in 180 (73.47%) followed by fever in 176 (71.84%) patients. Most common comorbidity found was hypertension in 89 (36.33%), followed by diabetes in 50 (20.44%). Conclusion: In this single-centred study, the characteristic features included presence of comorbidities, higher level of inflammatory markers, and high mortality rate in severe to critical hospitalised COVID-19 patients.